1996
DOI: 10.1116/1.588668
|View full text |Cite
|
Sign up to set email alerts
|

Titanium nitride coated tungsten cold field emission sources

Abstract: Comparison of tribological properties of carbon and carbon nitride protective coatings over magnetic mediaTitanium nitride ͑TiN͒ thin film coatings were studied by field emission microscopy and spectroscopy. Coated tungsten tips were found to be capable of emitting extremely high currents at low extraction voltages ͑ϳ1 mA at 900-1700 V͒. Current fluctuations for Ͼ400 A total emission from a single tip were 7% rms, measured over ϳ 1 h. Electron energy distributions measured Ͻ0.4 eV ͑full width at half-maximum͒.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Many studies have been conducted to find electron source materials with superior emission properties, for example, single-atom tips, 4–6 carbon nanotubes, 7–9 and etched sharp tips of borides, 10–26 carbides, 27–39 and nitrides. 40–46…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted to find electron source materials with superior emission properties, for example, single-atom tips, 4–6 carbon nanotubes, 7–9 and etched sharp tips of borides, 10–26 carbides, 27–39 and nitrides. 40–46…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to nd electron source materials with superior emission properties, for example, single-atom tips, [4][5][6] carbon nanotubes, [7][8][9] and etched sharp tips of borides, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] carbides, [27][28][29][30][31][32][33][34][35][36][37][38][39] and nitrides. [40][41][42][43][44][45][46] In particular, LaB 6 has been studied repeatedly since the 1970s because its low work function (WF) (2.1-2.6 eV) and chemical stability made it ideal as a TE emitter. Earlier studies of CFE from a LaB 6 tip found that the emission current was not sufficiently stable and decayed aer several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Metal carbides and nitrides are good candidates because they, like metal borides such as LaB 6 , have metallic, covalent, and ionic bonds simultaneously . There have been attempts to apply group 4 and 5 transition-metal carbides (TMCs) to an electron emitter. Similar attempts have been made for transition-metal nitrides (TMNs). …”
Section: Introductionmentioning
confidence: 99%
“…A field emission SEM has the highest magnification capability and is widely used in industries and research [2][3][4]. However, field emission SEMs are extremely expensive and require a high level of precautions, including an ultra high vacuum and a clean room, compared to thermionic SEMs.…”
Section: Introductionmentioning
confidence: 99%